Storytelling Marketing Communication Dalam Membangun Engagement Pada Nano Influencer Tiktok @Tenscoffeeid - Cahyaningrum, Nabila Pramudhita; Prasetya, Hendri; Mustiawan, Mustiawan (Jurnal Studi Ilmu Sosial dan Politik, 2025)
Purpose: TikTok has become one of the most influential marketing platforms, enabling brands to connect with audiences through short-form, narrative-driven content. For small brands and nano-influencers, storytelling is essential to stand out and build engagement. This study examines how the TikTok account @tenscoffeeid applies storytelling as a marketing communication strategy to engage its primarily student audience and explores how digital storytelling fosters emotional connections and promotes products effectively. Methodology/approach: This research used a qualitative case study approach. Data were collected through in-depth interviews, observation, documentation, and a literature review. Informants included the brand owner, account manager, and active audience members. Results/findings: The study found that the narrative-based content on @tenscoffeeid’s TikTok successfully created emotional connections with viewers and encouraged greater audience interaction. The storytelling strategy strengthened the brand’s identity and encouraged active participation from the audience through three key dimensions: consumption, contribution, and creation. Conclusions: Storytelling on @tenscoffeeid’s TikTok fosters engagement by aligning narratives with students’ experiences, responding to trends, and applying data-driven content planning. These findings show the potential of narrative strategies for small brands to build lasting audience relationships. Limitations: Focusing on student audiences may limit applicability to other groups, and cultural or platform differences were not examined. Contribution: This study contributes to the field of marketing communication and digital media studies by showing how storytelling on TikTok can be an effective tool for nano-influencers and small brands to build engagement. It provides insights for marketers, and and researchers in social media engagement and digital branding.